Threatened and Endangered Fish species in Nigeria, A Menace to Biodiversity – A Review - Emmanuel , Ekpo Imaobong; Abasi Ekpe, Asuquo, Idopise; Okon , Abiaobo, Nsikak (African Journal of Education,Science and Technology (AJEST), 2016)
Aquatic resources are important living forms that comprise biodiversity. The Nigerian aquatic environments play host to too many native and exotic aquatic resources. This article reviewed the survey of some endangered fish species and value for sustainable development in Nigeria. Studies showed many of the Nigerian fisheries resources are endangered due to habitat degradation, overfishing, and ornamental ventures consequently due to anthropogenic activities. Aquatic resources are important for the environmental sustainability, biodiversity conservation, tourism and human consumption. Fifteen fish families in Nigeria have been listed as being threatened and endangered and this list is on the increase with time as new species are found to be extinct. Commercially important and economically valued food-fish silver catfish, Chrysichthys nigrodigitatus, Heterotis niloticus and Erpetoichthys calabaricus have been reported to be threatened by factors such as destruction of breeding grounds, introduction of exotic species, habitat destruction, over exploitation, migration, water pollution and human activity. Conservation strategies were postulated as habitat restoration, closed season, registration of fishing gear, education and awareness campaign, protected area establishment, security patrol against illegal fishing, artificial breeding and legislation. It is therefore recommended that the government should intensify the awareness efforts on the danger of species extinction, as well as put in place measures towards the protection of endangered species for sustainable development, while researchers should also identify and have a checklist of these species.